Analysis and design of surface permanent magnet synchronous motor and generator - He, Chengyuan; Wu, Thomas (CES Transactions on Electrical Machines and Systems, 2019)
This paper presents an analytical method to design the high-efficiency surface permanent magnet synchronous motor (SPMSM) or generator (SPMSG). The air-gap and permanent magnet size can be approximately determined based on our mathematics model, which is the most important part of SPMSM design. From our method, we can know that motor's power out torque is related to the torque angle that we selected in our design and it affects the air-gap and permanent magnet size. If we choose a low torque angle, the motor or generator's overload power handing capability will increase. The embrace value has a vital place in designing a motor or generator due to its effects on air gap flux density, cogging torque, efficiency and so on. In order to avoid the knee effect, the working point of the permanent magnet we selected in the design should be bigger than 0.5. The developed 36 slots, 4 poles, surface mound permanent generator is proposed. The corresponding finite element analysis (FEA) model is built based on our design method. Structure optimization includes stator and rotor structure size, permanent magnet size, magnetic bridge and air gap length which are analyzed and simulated by ANSYS Maxwell 2D FEA. Thermal analysis is conducted, and the housing of the alternator is designed. The alternator prototype is fabricated and tested based on our design.